Make public: performing public housing in Ernő Goldfinger's Balfron Tower. Issue 1 (2nd January 2017) - Roberts, David
Abstract : To 'make public' expresses three aims that have driven my doctoral research into the past and future of east London housing estates undergoing regeneration; materially – to protect public housing provision at a time when austerity measures are dismantling it in ideal and form; procedurally – to make visible problematic processes of urban change that are increasingly hidden from public view; and methodologically – to make public my act of research through intimate and sustained collaboration with residents on site. This research document focuses on Balfron Tower, a high-rise of 146 flats and maisonettes arranged on 26 storeys built in 1965–7, the first phase of émigré architect Ernő Goldfinger's work on the Greater London Council's (GLC) Brownfield Estate in Poplar. In December 2015, the London Borough of Tower Hamlets approved plans to refurbish and privatise Balfron Tower. In this paper, I describe my collaborative work with the tower's current and former residents in the preceding three years during which we campaigned for Balfron to remain a beacon for social housing. I structure the paper on the three phases this work followed; analysis of cultural, academic and archival material which foregrounds both the persistent accusations of failure that have afflicted the tower and the egalitarian principles integral to its vision and function as social housing; engagement with residents re-enacting Goldfinger's own methods of gathering empirical evidence in 1968, and; activism drawing on this material and evidence to contribute to informed public debate and planning decisions. Through this paper, I illustrate how Balfron's history was mobilised to commodify the tower on the one hand, and to interrogate and object to this process on the other. In doing so, I advance an argument that the practice and guidance of heritage of post-war housing estates must not only pay tribute to the egalitarian principles at their foundations, it must enact them.